Innovation in Family Card Issuance Services According to Law no. 24 of 2013 in Efforts to Implement E-Government in Sumber Suko Village - Andika, Verto Septi; Fadilah, Siti Nur; Karimah, Zahrotul; P, Nur Adinda; P, Ervito Setya (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
Goverment Including electronic-based public services that aim to help the community in the implementation of government access. One of them is in the field of Population Administration Services in Family Card Issuance Innovation According to Uu No. 4 of 2013 In an Effort to Implement E-Government in Sumber Suko Village, this research will discuss Family Card Issuance Innovation According to Uu No. 24 of 2013 In an Effort to Implement E-Government in Sumber Suko Village. This research uses a qualitative method where the results of the research have no element of calculation. However, this research is in the form of Documentation and interviews. Based on the research that has been carried out, the author concludes that Quality and Services or other administrative administrations in Family Card Publishing Innovation According to Uu No. 24 of 2013 In an Effort to Implement E-Government in Sumber Suko Village It is quite perfect but still lacking in the participation of the community in developing the efficiency of implementing E-Goverment in the village.